Energy markets, financing and accounting – Special issue from the 2017 International Conference on Energy & Environment - Soares, Isabel; Ferreira, Paula; Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2018)
This editorial introduces the 15th volume of the International Journal of Sustainable Energy Planning and Management. The volume is a special issue from the 2017 International Conference on Energy & Environment, Porto, Portugal and it presents work on energy markets, energy financing and accounting of energy projects.